Applications of Monolayer‐Functionalized H‐Terminated Silicon Surfaces: A Review. Issue 4 (22nd March 2017) - Veerbeek, Janneke; Huskens, Jurriaan
Abstract : Silicon is an attractive semiconductor material for wide‐ranging applications, from electronics and sensing to solar cells. Functionalization of H‐terminated silicon surfaces with molecular monolayers can be used to tune the properties of the material toward a desired application. Several applications require the removal of the, often insulating, silicon oxide between the silicon surface and a monolayer, thus precluding the more conventional silane‐based chemistry. Here, the applications of monolayer‐functionalized silicon surfaces are surveyed starting from H‐terminated silicon. The oxide‐free routes available for Si–C, Si–N, Si–O–C, and Si–S bond formation are described, of which the most commonly used techniques include hydrosilylation and a chlorination/alkylation route onto H‐terminated silicon. Applications are subdivided into the areas of surface passivation, electronics, doping, optics, biomedical devices, and sensors. Overall, these methods provide great prospects for the development of stabilized silicon micro‐/nanosystems with engineered functionalities. Abstract : The applications of molecular monolayers on H‐terminated silicon are reviewed. An overview of the routes toward covalent, oxide‐free monolayer formation is given, i.e., the techniques that result in Si–C, Si–N, Si–O–C, and Si–S bond formation. Applications reported for these surfaces are subdivided into the areas of surface passivation, electronics, doping, optics, biomedical devices, and sensors.